Feminization of the Nile tilapia Oreochromis niloticus by estradiol-17? Effects on growth, gonadal development and body composition - Alcántar Vázquez, Juan Pablo; Rueda Curiel, Paola; Calzada Ruíz, Daniel; Antonio Estrada, Carolina; Moreno de la Torre, Raúl (Universidad Autónoma Metropolitana: Hidrobiológica, 2015)
Conditions for the feminization of undifferentiated XY fry of Nile tilapia (Oreochromis niloticus) fed on a diet supplemented with estradiol-17? (E2) were investigated in order to produce functional phenotypical females (genetic males). Different E2 concentrations (60 and 120 mg kg-1) were tested over a period of 30 days in a closed recirculating system. Fry were fed ad libitum at 1-h intervals. The effects on growth, gonadal development and body composition were evaluated at sexual maturity. Sex-reversed females were produced in both E2 treatments. The proportion of males was significantly lower (p < 0.05) in both E2 treatments compared to the control group. Fish with atypical papilla and normal ovaries were produced in both E2 concentrations. These fish were considered sex-reversed females. Growth was significantly higher (p < 0.05) in the males compared to both the females and the sex-reversed ones in all groups analyzed. No testicular tissue was observed in any of the ovaries of the sex-reversed females analyzed. The percentage of fat in muscle increased and that of protein decreased significantly (p < 0.05) in the sex-reversed females compared to that observed in the control group. Identified sex-reversed females will be used in the production of YY males through mating with normal males, as part of a developing breeding program to produce a male genetic population in the southern region of Mexico.
Keywords: Tilapias; Estradiol-17β